Influence of the selective serotonin re‐uptake inhibitor, paroxetine, on gastric sensorimotor function in humans - Tack, J.; Broekaert, D.; Coulie, B.; Fischler, B.; Janssens, J. (Alimentary pharmacology & therapeutics, 2003)
Summary Background : The role of 5‐hydroxytryptamine in the control of gastric fundus tone in humans is still unknown. Selective 5‐hydroxytryptamine re‐uptake inhibitors act both centrally and peripherally to enhance the availability of physiologically released 5‐hydroxytryptamine. Aim : To study the influence of a selective 5‐hydroxytryptamine re‐uptake inhibitor, paroxetine, on gastric fundus tone, on the perception to gastric distension and on gastric accommodation to a meal. Methods : Sixteen healthy volunteers underwent a gastric barostat study on two occasions, after pre‐treatment with placebo or paroxetine, 20 mg/day. Graded isobaric and isovolumetric distensions were performed and perception was scored by a questionnaire. Subsequently, the amplitude of the gastric accommodation to a mixed liquid meal was also measured. Results : Pre‐treatment with paroxetine did not alter the thresholds for perception and discomfort during isobaric (4.7 ± 2.3 vs. 4.0 ± 2.0 mmHg and 13.3 ± 3.1 vs. 12.7 ± 2.3 mmHg above the minimum intragastric distending pressure, N.S.) and isovolumetric (307 ± 90 vs. 417 ± 114 mL and 772 ± 74 vs. 750 ± 76 mL, N.S.) distensions. Paroxetine significantly enhanced the amplitude of the meal‐induced fundus relaxation (136 ± 51 vs. 255 ± 43 mL, P < 0.05). Conclusions : Pre‐treatment with paroxetine enhances gastric accommodation to a meal. These data suggest that the release of 5‐hydroxytryptamine, probably at the level of the enteric nervous system, is involved in the control of the accommodation reflex in humans, and that paroxetine may be beneficial to patients with impaired post‐prandial fundus relaxation.